CHOROIDAL MELANOMA IN PHAKOMATOSIS PIGMENTOVASCULARIS WITH OVERLAPPING STURGE–WEBER SYNDROME AND KLIPPEL–TRENAUNAY SYNDROME. Issue Volume 17:Issues 2(2023) (March 2023) - Fry, Matthew V.; Williams, Basil K.; Kim, Hyun Jun; Di Nicola, Maura
Abstract : Nevus flammeus is present in Sturge–Weber and Klippel–Trenaunay syndromes, both associated with diffuse choroidal hemangioma. It is also associated with ocular melanocytosis, predisposing patients with phakomatosis pigmentovascularis to uveal melanoma. Given the overlap between these conditions, patients with nevus flammeus and an intraocular mass should be assessed for uveal melanoma. Abstract : Purpose: To present the rare occurrence of choroidal melanoma in an adult patient with phakomatosis pigmentovascularis and an overlap of Sturge–Weber syndrome and Klippel–Trenaunay syndrome. Methods: Observational case report. Results: A 75-year-old White woman with nevus flammeus involving the left forehead, periorbital area, cheek, chin, upper limb, and trunk, along with hemihypertrophy of the left side of the face and left upper limb, presented for evaluation of an intraocular mass in the left eye. Anterior examination of the left eye showed diffuse episcleral and iris melanocytosis. Fundus examination of the left eye showed diffuse choroidal melanocytosis and an elevated choroidal lesion. B-scan ultrasonography demonstrated a hollow lesion, and the patient was diagnosed with choroidal melanoma in the left eye in the setting of phakomatosis pigmentovascularis with overlap of Sturge–Weber syndrome and Klippel–Trenaunay syndrome. Fine-needle aspiration biopsy confirmed the diagnosis, and Iodine 125 plaque radiotherapy was performed. Conclusion: Individuals with clinical features suggestive of phakomatosis pigmentovascularis, Sturge–Weber syndrome, or Klippel–Trenaunay syndrome should undergo a complete ophthalmological evaluation for the presence of ocular melanocytosis and uveal melanoma.